SUSTAINABLE LAND MANAGEMENT AS AN INSTRUMENT TO IMPROVE ECOLOGICAL AND ECONOMIC EFFICIENCY OF AGRICULTURAL LAND USE - Valentina GAMAJUNOVA; Oksana ISKAKOVA; Volodymyr YANCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The goal of the research is to substantiate scientific and institutional fundamentals of sustainable land management as an instrument to improve economic efficiency of agricultural land use. The research methodology is presented as a model of the system of measures, which should be performed while adapting to the sustainable development of agricultural land management being the instrument to improve ecological and economic efficiency of land resources use. The research progress included implementation of several stages: 1) analysis of the goals of sustainable development, adapted for Ukraine for the period of 2015-2030; 2) determination of the specificity of use of the region’s land and resource potential; 3) assessment of the impact of agro-technical and natural-climatic factors on the value of yield by the dispersion analysis method;4) modeling of the current and expected levels of yield of grain and soil-exhausting crops in conditions of the studied territory. To supply automation of the dispersion analysis calculations, the researchers used the computer program “Regre”. The described methodology was tested on the territory of Mykolaiv region. The research defined the impact of agro-technical and natural-climatic factors on the value of yield capacity of the main agricultural crops of the region and their distinction by applying the dispersion analysis method. The research results are used to make forecasts of the level of yield of grain crops and sunflower in the future (2025). The increased yields of the main crops will provide the possibility to reduce the area of agricultural plowing, as well as expand the area of lands used for nature protection. The economic balance for the security of sustainable land management of the examined region needs crucial improvements. First, it concerns revival of land-owners’ careful attitude to land. Therefore, labour and financial efforts should be focused on active application of the tools of the mechanism of land resources reproduction.